Acetaminophen Induces an Antioxidative Response in Lettuce Plants - Inês Leitão; Luisa L. Martins; Luisa Carvalho; M. Conceição Oliveira; M. Matilde Marques; Miguel P. Mourato (Plants, 2021)
Contaminants of environmental concern, like pharmaceuticals, are being detected in increasing amounts in soils and irrigation waters and can thus be taken up by plants. In this work, the uptake of acetaminophen (ACT) by lettuce plants was evaluated through a hydroponic experiment at different concentrations (0, 0.1, 1 and 5 mg L−1 ACT). The pathways related to oxidative stress induced by ACT were studied in lettuce leaves and roots at 1, 8 and 15 days after exposure. Stress indicators such as hydrogen peroxide and malondialdehyde (MDA) contents were analyzed, revealing increases in plants contaminated with ACT in comparison to control, confirming the occurrence of oxidative stress, with the exception of MDA in leaves. The enzymatic activities of catalase, superoxide dismutase, guaiacol peroxidase, ascorbate peroxidase and glutathione peroxidase, directly involved in the antioxidative system, showed significant differences when compared to control plants, and, depending on the enzyme and the tissue, different trends were observed. Glutathione reductase revealed a decrease in contaminated leaves, which may imply a specific impact of ACT in the glutathione cycle. Significant increases were found in the anthocyanin content of leaves, both with exposure time and ACT concentration, indicating an antioxidative response induced by ACT contamination.